PENGARUH TERAPI BEKAM KERING TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DESA BINAWARA KECAMATAN KUSAN HULU KABUPATEN TANAH BUMBU TAHUN 2018 - Siska Agistin; Farhandika Putra; Bayu Purnama Atmaja (NHM PRESS, 2019)
Dry cupping is one of the complementary treatments that serves to widen the narrowed blood vessels. Hypertension is a condition when a person experiences a rise in blood pressure above normal. The aim of this study was to determine the effect of dry cupping therapy on the reduction of hypertension in Desa Binawara Kecamatan Kusan Hulu kabupaten Tanah Bumbu 2018.The study design was Quasi Experimental with Pretest Postest Without Control. The sample of this study were patients who had hypertension in the Desa Binawara a and were given the dry cupping therapy as much as 1 time that were 25 respondents with purposive sampling technique.The results of this study by using the Wilcoxon test obtained the results of pretest Hypertension Degree 2 (16.0%) Hypertension grade 1 and posttest (8.0%) Pre Hypertension with p value 0.001 (˂ 0.05).Conclusion, there was an effect of giving dry cupping therapy to a decrease in hypertension in Desa Binawara Kecamatan Kusan Hulu kabupaten Tanah Bumbu 2018. It was recommended for hypertensive patients to routinely in order to carry out routine checks on blood pressure and make a healthy lifestyle in consuming food.